Knitted breathing sensor - Ehrmann, Andrea; Heimlich, F.; Brucken, A.; Weber, M. O.; Haug, R. (Melliand Textilberichte)
Fabrics knitted from conductive fiber yarns containing stainless steel wires show a strong dependence of the electrical conductivity on elongation. This behavior can be utilized to knit a textile breathing sensor. In order to assure a sufficient reproducibility, the choice of the structure is essential.